Is Pulley Reconstruction Better Than Pulley Release for De Quervain's Tenosynovitis? A Double-Blind Randomized Controlled Trial - Salim, Burhan; Ansari, Mohammed Tahir; Kumar, Venkatesan Sampath; Goyal, Ankur; Malhotra, Rajesh (Journal of Wrist Surgery, 2021)
Purpose The aim of this study was to compare the results of surgeries of the De Quervain's disease (DQD) through a randomized control trial.Materials and Methods We treated 40 cases of De Quervain's tenosynovitis in 2 groups: 20 patients by pulley release method and another 20 patients by pulley reconstruction method. The patients were selected as per the random table number. The clinical data, numeric Visual Analogue Scale (VAS) score, Quick DASH—Disabilities of the Arm, Shoulder, and Hand—score, Mayo Wrist Score, and subluxation of the tendons in dynamic ultrasonography (USG) during wrist hyperflexion and abduction of the thumb test were noted preoperatively and 6 months after the operation. All patient charts were reviewed and data analysis was done after completion of the study.Results All patients improved after surgery. There was no difference in clinical outcome data, numeric VAS score, Quick DASH Score, and Mayo Wrist Score (p-value > 0.05). There were four patients with tendon subluxation under USG in pulley release group, out of which only one patient was clinically symptomatic. There was no tendon subluxation in pulley reconstruction group. The tendon subluxation between the two groups was not found to be statistically significant (p-value: 0.661).Conclusion Although, higher numbers of subluxation were found in release group, there was no statistically significant difference in the outcome of the two surgical procedures for DQD. This study is a pilot study, and it may act as the groundwork over which further studies may be performed.Level of Evidence This is a Level I study.
Keywords: De Quervain; tenosynovitis; extensor; pulley; first extensor compartment